Internalization of Religious Moderation Values within the Integrative Curriculum of Satuan Pendidikan Muadalah (SPM) Al-Khairy Praya, Central Lombok - Hamdan Hamdan; MZ Muttaqien H. Lagala; Muslihan Muslihan (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study objectives to analyze the internalization of religious moderation values within the integrative curriculum at Satuan Pendidikan Muadalah (SPM) Al-Khairy Praya, Central Lombok. A qualitative-descriptive research design was employed as the method. The research instruments consisted of structured interview guides, observation checklists, and documentation review sheets. Data collection techniques included in-depth interviews with the school administrators and teachers, non-participant observation of classroom activities, and academic document analysis. The data analysis techniques followed the interactive model comprising data condensation, data display, and conclusion drawing. The results indicated that the internalization process is systematically executed through epistemological integration in course materials, the contextualization of classical Islamic texts (turats) regarding modern social reality, and cultural habituation within the pesantren environment. In conclusion, the integrative curriculum successfully embeds moderation values organically, fostering open-minded, tolerant, and nationalistic student perspectives. This model provides an empirical benchmark for high-quality academic standardization in Islamic educational institutions.